Beneficial effects of dietary docosahexaenoic acid intervention on cognitive function and mental health of the oldest elderly in Japanese care facilities and nursing homes. Issue 2 (28th January 2016) - Hashimoto, Michio; Kato, Setsushi; Tanabe, Yoko; Katakura, Masanori; Mamun, Abdullah Al; Ohno, Miho; Hossain, Shahdat; Onoda, Keiichi; Yamaguchi, Shuhei; Shido, Osamu
Abstract : Aim: We examined the effects of the administration of docosahexaenoic acid (DHA)‐enriched meals on cognitive function in the oldest elderly with cognitive impairment, such as dementia, living in nursing homes, and on the improvement in caregiver burden at aging agencies. Methods: Participants in elderly care facilities and nursing homes ( n  = 75; 88.5 ± 0.6 years) were randomized in active and placebo groups. The active group had family‐style meals containing an additional 1720 mg of docosahexaenoic acid per day for 12 months. At baseline, and after 6 and 12 months of intervention, cognitive function was assessed using Hasegawa's Dementia Scale‐Revised and the Mini‐Mental State Examination; mental health condition was assessed with the Apathy scale and the Zung Self‐Rating Depression Scale; caregiver burden was evaluated using Zarit Burden Interview scores; and participants' serum biochemical factors were measured. Results: The participants were suggested to have dementia. After 12 months, the mean change in Mini‐Mental State Examination subitem "Registration" score from baseline to month 12 showed a tendency to be greater in the active group than that in the placebo group. Mean changes in the Apathy scale from baseline to month 12 were less, and the changes in the Zung Self‐Rating Depression Scale and the total Zarit Burden Interview scores showed a tendency to be lower in the active group than in the placebo group, respectively. Conclusion: These results suggest that docosahexaenoic acid‐enriched meals protect against age‐related cognitive decline, and also improve apathy and caregiver burden for the oldest‐elderly Japanese with cognitive impairment, such as dementia.Geriatr Gerontol Int 2017; 17: 330–337.